The Government of Canada and Intangible Cultural Heritage: An Excursion into Federal Domestic Policies and the UNESCO Intangible Cultural Heritage Convention - Pocius, Gerald (Ethnologies, 2014)
Over the past twenty years, what constitutes a culture’s heritage has been debated amongst those responsible for governmental policies, as well as the constituents that governments serve. While heritage has often focused on tangible items – architecture and the material world – recent policies have broadened the focus to include the intangible: knowledge, ideas, performances, beliefs handed down for generations. Many national and international agencies – lead by UNESCO – now have policies and programs that deal with intangible cultural heritage (ICH). Within the Canadian context, the federal government has had differing interpretations of the importance of this type of heritage. Most recently, in spite of initial involvement in its drafting, the Department of Canadian Heritage has decided not to support UNESCO’s new international ICH Convention, which went into force in April, 2006, and now includes more than 160 countries that have ratified it. Historically, provincial governments and NGOs across Canada have been more involved with ICH, and it is here that the most recent initiatives are occurring. The changing stance of the Department of Canadian Heritage on this topic may well be related to specific figures involved, unspoken fears of legal repercussions, and the lobbying of special interest heritage groups.